A Comprehensive Conceptualization of Post-Adoptive Behaviors Associated with Information Technology Enabled Work Systems1 - Jasperson, 'Jon (Sean); Carter, Pamela E.; Zmud, Robert W. (MIS Quarterly, 2005)
For the last 25 years, organizations have invested heavily in information technology to support their work processes. In today’s organizations, intra-and interorganizational work systems are increasingly IT-enabled. Available evidence, however, suggests the functional potential of these installed IT applications is underutilized. Most IT users apply a narrow band of features, operate at low levels of feature use, and rarely initiate extensions of the available features. We argue that organizations need aggressive tactics to encourage users to expand their use of installed IT-enabled work systems. This article strives to accomplish three primary research objectives. First, we offer a comprehensive research model aimed both at coalescing existing research on post-adoptive IT use behaviors and at directing future research on those factors that influence users to (continuously) exploit and extend the functionality built into IT applications. Second, in developing this comprehensive research model, we provide a window (for researchers across a variety of scientific disciplines interested in technology management) into the rich body of research regarding IT adoption, use, and diffusion. Finally, we discuss implications and recommend guidelines for research and practice.